Tragedie Piotra Krasuskiego wobec sztuki wymowy - Pirecki, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article is the first attempt systematize the therm rhetoric of the tragedy Piotr Krasuski. It also methodizes other tragedy genres. The readers gives a great insight into considerations about the tragedy by Piotr Krasuski and historical background. Moreover, the final remarks are to confirm the established thesis of the research work.